2020
DOI: 10.37212/jcnos.715227
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam modulates hypoxia-induced inflammation and oxidative stress via inhibition of TRPV1 channel in the DBTRG glioblastoma cell line

Abstract: Levetiracetam modulates hypoxia-induced inflammation and oxidative stress via inhibition of TRPV1 channel in the DBTRG glioblastoma cell line Kemal Ertilav 895 IDH1 R132H gene mutation reduces cell proliferation and sensitizes recurrent Glioblastoma to hydrogen peroxide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…The inhibition of RPL‐induced increase of caspase‐3, and caspase ‐9 but the decrease of cell viability by the treatments of ACA and CPZ as well as the LMWH treatment suggested the important role of [Ca 2+ ] i , TRPM2, and TRPV1 in the induction of apoptosis. In addition to the stimulation of [Ca 2+ ] i increase dependent‐caspase‐3 and caspase‐9 pathways of apoptosis, [Ca 2+ ] i signal via the stimulation of TRPM2 and TRPV1 was found to alter the MiMP that might be critical for the induction of apoptosis 12,24–26,34,35 . Consistently, the results in the current study revealed that RPL increase MiMP levels, which was found to be attributable to the changes in the [Ca 2+ ] i concentration as evidenced by the preventive actions of ACA and CPZ, antagonists of TRPM2 and TRPV1.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The inhibition of RPL‐induced increase of caspase‐3, and caspase ‐9 but the decrease of cell viability by the treatments of ACA and CPZ as well as the LMWH treatment suggested the important role of [Ca 2+ ] i , TRPM2, and TRPV1 in the induction of apoptosis. In addition to the stimulation of [Ca 2+ ] i increase dependent‐caspase‐3 and caspase‐9 pathways of apoptosis, [Ca 2+ ] i signal via the stimulation of TRPM2 and TRPV1 was found to alter the MiMP that might be critical for the induction of apoptosis 12,24–26,34,35 . Consistently, the results in the current study revealed that RPL increase MiMP levels, which was found to be attributable to the changes in the [Ca 2+ ] i concentration as evidenced by the preventive actions of ACA and CPZ, antagonists of TRPM2 and TRPV1.…”
Section: Discussionsupporting
confidence: 86%
“…The TRPM2 is activated by the PARP‐1 stimulation‐mediated ADP‐ribose generation 19,21,34 . Hence, we performed the PARP‐1 protein band levels in the thrombocytes of Ctr, patient, and treatment (LMWH) groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations